Ecomorphology in dragonfly Neurothemis fluctuans - Norma-Rashid, Y. (Malaysian Journal of Science, 1999)
The ’bigger is better’ hypothesis is examined on dragonflies by using an ecomorphological approach. Preliminary evidence indicate that optimum fitness, as measured by the survivorship and resource holding potential, favours medium-sized males. Population differences in body parts measurements were not obvious but size sexual dimorphism was negatively correlated,